2005
DOI: 10.1080/02841860510007549
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and determinants of the use of complementary and alternative medicine in adult Turkish cancer patients

Abstract: A study was undertaken to analyze the extent of using complementary alternative medicine (CAM) and to compare sociodemographic and medical characteristics of users and non-users of CAM in Turkish oncology patients. A total of 615 patients with cancer who attended ambulatory patient care units answered the questionnaires. Medical information was reviewed from chart data. Some 291 patients (47.3%) had used at least one type of CAM since the time of initial diagnosis. CAMs almost always consisted of herbal agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
92
3
12

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(123 citation statements)
references
References 9 publications
16
92
3
12
Order By: Relevance
“…Our finding that fewer than half the patients in our study discussed their use of CAM with their physicians is in agreement with studies done in Turkey (21.3%) (Tas et al, 2005) and Japan (39.3%) (Hyodo et al, 2005) but not in the U.S. (89.1%) (McEachrane-Gross et al, 2006). That few (1.6%) received recommendations for CAM use by their physicians is consistent with studies done in Japan (Hyodo et al, 2005) and Europe (Molassiotis et al, 2005), however it did not consistent according to geographic variance (Risberg et al, 2003).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our finding that fewer than half the patients in our study discussed their use of CAM with their physicians is in agreement with studies done in Turkey (21.3%) (Tas et al, 2005) and Japan (39.3%) (Hyodo et al, 2005) but not in the U.S. (89.1%) (McEachrane-Gross et al, 2006). That few (1.6%) received recommendations for CAM use by their physicians is consistent with studies done in Japan (Hyodo et al, 2005) and Europe (Molassiotis et al, 2005), however it did not consistent according to geographic variance (Risberg et al, 2003).…”
Section: Discussionsupporting
confidence: 82%
“…Predictors of CAM in Western countries, however, include being female (Molassiotis et al, 2005;Risberg et al, 2003), younger (Burstein et al, 1999;Risberg et al, 2003), more highly educated (Kao and Devine, 2000;Lerner and Kennedy, 1992), employed (Verhoef et al, 2005), professional (Downer et al, 1994), and having a higher income (Kao and Devine, 2000;McEachrane-Gross et al, 2006), while other studies showed inconsistent associations (Navo et al, 2004) or none (Tasaki et al, 2002). Although several studies report no relationship between CAM use and conventional treatment (McEachrane-Gross et al, 2006), advanced stage (Tas et al, 2005), or disease site (Fernandez et al, 1998), patients with lymphoma or cancer of the brain or CNS tend to use CAMs. The stereotype that terminally ill, desperate, uneducated patients are the primary users of CAM is inaccurate (Lafferty et al, 2006).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The possible explanation for this behavior is being less educated, having a lower income, and a 'traditional society structure'. 2,3,9 In Turkish culture, the most commonly used herb is reported as nettle leaves/teas and thyme, often mixed with other compounds. Availability is very easy and has a suitable price.…”
Section: Discussionmentioning
confidence: 99%
“…Among cancer patients, CAM is considered as natural, non-toxic, and has health promoting effects. 2,3 Therefore, CAM is very popular among cancer patients and gives them hope for a cure. In addition, these patients want to try all therapies other than modern therapies.…”
Section: Introductionmentioning
confidence: 99%